Bacteria in agrobiology: stress management - Maheshwari, Dinesh K. (Springer Berlin Heidelberg, 2012)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. "Bacteria in Agrobiology: Stress Management" covers the major aspects on PGPR in amelioration of both abiotic and biotic stresses. PGPR mediated in priming of plant defense reactions, nutrient availability and management in saline and cold environment, hormonal signaling, ACC deaminase and its role in ethylene regulation under harsh conditions are suitably described.